2015
DOI: 10.5539/ies.v8n12p141
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Entrepreneurship Education on the Entrepreneurial Intentions of Students in Technical and Vocational Education and Training Institutions (TVET) In Malaysia

Abstract: The purpose of this study was to determine the entrepreneurial intention level of vocational and technical students in Malaysia. A total of 289 final year students who were enrolled at two different TVET institutions (community colleges and National Youth and Skills Institutes) were chosen to participate in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 20 publications
3
47
1
1
Order By: Relevance
“…Research findings (Kuttim et al, 2014;Kim-Soon et al, 2016) showed that participation in entrepreneurship education has a positive effect on students' entrepreneurial intentions. There is a significant relationship between entrepreneurial intention and entrepreneurship education (Hussain & Norashidah, 2015;Lorz, 2011;Hattab, 2015;Ibrahim et al, 2015), through students' involvement in experiential and existential lifelong learning practices (Robinson et al, 2016), and through developing meaning of action, reflections, and experience (Hagg & Kurczewska, 2016). Moreover, the role of entrepreneurship education delivered to students is able to improve their achievement orientation, personal control, and self-esteem (Basardien et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research findings (Kuttim et al, 2014;Kim-Soon et al, 2016) showed that participation in entrepreneurship education has a positive effect on students' entrepreneurial intentions. There is a significant relationship between entrepreneurial intention and entrepreneurship education (Hussain & Norashidah, 2015;Lorz, 2011;Hattab, 2015;Ibrahim et al, 2015), through students' involvement in experiential and existential lifelong learning practices (Robinson et al, 2016), and through developing meaning of action, reflections, and experience (Hagg & Kurczewska, 2016). Moreover, the role of entrepreneurship education delivered to students is able to improve their achievement orientation, personal control, and self-esteem (Basardien et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Study findings (Kuttim et al, 2014;Kim-Sun et al, 2016) demonstrated that entrepreneurship education has a significant effect on entrepreneurial intentions of students. A significant association is observed between entrepreneurship education and entrepreneurial intention (Hussain, 2015;Hattab, 2015;Ibrahim et al, 2015), by students' participation in permanent existential and experiential learning practices (Robinson et al, 2016) and by developing the meaning of reflection, experience and action (Hagg and Kurczewska, 2016). Also, entrepreneurship education aims to improve students' achievement orientation, self-esteem and personal control (Basardien et al, 2016;Mahendra et al, 2017).…”
Section: Entrepreneurship Education Role On Entrepreneurial Intentionsmentioning
confidence: 99%
“…An interesting study that was done found that students that experienced entrepreneurship education are more inclined to have better entrepreneurial aspirations as compared to students who were not exposed to entrepreneurship courses (Gerba 2012). More knowledge about entrepreneurship education can result in students having more convincing views on entrepreneurship interest (Ibrahim, Bakar, Asimiran, Mohamed, & Zakaria, 2015). More emphasis should be placed on students, to pursue entrepreneurship education.…”
Section: Exposurementioning
confidence: 99%